Heterogeneous evolution of SARS-CoV-2 seroprevalence in school-age children - Sarah R. Haile; Alessia Raineri; Sonja Rueegg; Thomas Radtke; Agne Ulyte; Milo A. Puhan; Susi Kriemler (Swiss Medical Weekly, 2023)
BACKGROUND: Much remains unknown regarding the evolution of SARS-CoV-2 seroprevalence and variability in seropositive children in districts, schools and classes as only a few school-based cohort studies exist. Vaccination of children, initiated at different times for different age groups, adds additional complexity to the understanding of how seroprevalence developed in the school aged population.